2013
DOI: 10.5098/hmt.v3.4.3006
|View full text |Cite
|
Sign up to set email alerts
|

SLIP EFFECTS ON BOUNDARY LAYER FLOW AND MASS TRANSFER WITH CHEMICAL REACTION OVER A PERMEABLE FLAT PLATE IN A POROUS MEDIUMn over a permeable flat plate in a porous medium

Abstract: A mathematical model is presented to analyse the steady boundary layer slip flow and mass transfer with n th order chemical reaction past a porous plate embedded in a Darcy porous medium. Velocity as well as mass slips are considered at the boundary. The governing PDEs are transformed into self-similar nonlinear ODEs by similarity transformations. The reduced nonlinear equations are solved numerically. The momentum boundary layer thickness is reduced for increase of permeability and suction parameters, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
(25 reference statements)
2
5
0
Order By: Relevance
“…Physically, an increase in leads to the increase in the number of solute molecules undergoing chemical reaction resulting in decrease in the fluid field. This is similar to results observed by Damesh and Shannak [45] for viscoelastic fluid, and Bhattacharyya [46] for viscous fluid. Furthermore, one can come to the conclusion from Figs.…”
Section: The Effect Of Viscosity Ratio Msupporting
confidence: 91%
“…Physically, an increase in leads to the increase in the number of solute molecules undergoing chemical reaction resulting in decrease in the fluid field. This is similar to results observed by Damesh and Shannak [45] for viscoelastic fluid, and Bhattacharyya [46] for viscous fluid. Furthermore, one can come to the conclusion from Figs.…”
Section: The Effect Of Viscosity Ratio Msupporting
confidence: 91%
“…We obtain a numerical solution of the problem given by the governing Equation 18together with Conditions (19)- (21). The discretized form of Equation 18is presented using a finite difference scheme in ref.…”
Section: Numerical Solutionmentioning
confidence: 99%
“…there are situations where this condition is not adequate in that the flow may exhibits slip effect [21] [22] [23] [24] [25]. It has been experimentally verified that the slip effects become important in nanochannels and micro channels (see [26]).…”
Section: Introductionmentioning
confidence: 99%
“…They found that the increase of velocity slip parameter reduces the momentum boundary layer thickness and enhances the heat transfer from the plate; on the other hand, heat transfer decreases with thermal slip parameter. Bhattacharyya [9] considered velocity and mass slips at the boundary in the analysis of the steady boundary layer flow and mass transfer with nth order chemical reaction past a porous plate embedded in a Darcy porous medium. The reduced nonlinear equations were solved numerically.…”
Section: Introductionmentioning
confidence: 99%